Metode Diskusi Dalam Meningkatkan Hasil Belajar Pak Pada Peserta Didik Kelas III SDN 025 Teluk Binjai Kota Dumai - Manatap Sitorus (Jurnal Pusat Studi Pendidikan Rakyat, 2022)
This study aims to determine the benefits of using the discussion method in improving student learning outcomes in the subject of Catholic Religious Education. This study uses a Classroom Action Research approach. The subject of this research is a teacher and third grade student of SD Negeri 025 Teluk Binjai, Dumai City. The results of the study can be described in the implementation of cycle I and cycle II. In the first cycle, it was obtained information on the learning outcomes of students with the class average score of 72.33 from 15 students. Of the 15 students, there are 9 people who are in the Completed category, and 6 people who are in the Unfinished category. In the implementation of the second cycle of action, it was obtained that the class average score was 85.33 from 13 students. Of the 15 students, there are 13 people who are in the Completed category, and 2 people who are in the Unfinished category. The results of the observation cycle I and cycle II showed a significant change in the achievement of student learning outcomes. This change indicates that the use of the discussion method in learning Catholic Religious Education has been able to improve student learning outcomes in class III SD Negeri 025 Teluk Binjai, Dumai City.